The Relationship between Family and Community Resilience during the Developmental Transition of Emerging Adulthood - Garcia, Elisabeth Ponce; McNeill, Charleen; LCSW, Grace Whaley; Rohli, Robert V; Garrison, M. E. Betsy (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
Resilience – the ability of a dynamic system to withstand, or adapt to, threats or risk to its stability, viability, or development – is an important component of environmental, economic, and social systems. While resilience has been studied extensively from individual-, family-, and community-level perspectives, substantially less work has been devoted to understanding resilience through a lens that crosscuts system levels so that an integrated model of resilience can be developed. This research aims to address this gap by identifying a link between family and community resilience as reported by 593 emerging adults. Results support the hypothesis that family resilience predicts community resilience during the transition to adulthood. The results support the proposed framework presented by Houston (2018) in which community resilience is positioned well for both top-down and bottom-up comparisons. The results are also consistent with the dynamic systems perspective which posits that resilience occurs as a result of interactions between and within the levels of complex systems to include the individual, family, and community. These results assist in understanding mechanisms by which resilience emerges from internal and external interactions between and within levels of each system and across developmental transitions.